PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 005 LENGGADAI HILIR KECAMATAN RIMBA MELINTANG KABUPATEN ROKAN HILIR - Suryadi Suryadi; Zetra Hainul Putra; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Background of this research is the low of science learning result of grade V SDN 005 Lenggadai Hilir. To improve it, the researchers apply cooperative learning model make a match type. This research uses classroom action research. The research is done in two cycles in which each cycle consists of two meetings and a test. Subject in this research is 28 fourth grade students, 12 males and 16 females. The data is got from observation of teacher’ and students’ activity during the learning process and the result of students examination in the end of each cycle. The result of the research shows that there is an increase of science learning result of grade IV SDN 005 Lenggadai Hilir after learning activities using cooperative learning model make a match type. This can be seen from the students’ average scores. The result of student learning is categorized low in the beginning by average 60,03. Nevertheless at the first cycle (I) increases into 70,75, and raises again into 77,50 in the second cycle. Teacher’s activity in the first meeting of first cycle is 60% by fair category, and 65% by good category in the second meeting. In the second cycle (II) at first meeting teachers’ activity is 67% by good category and increases in the second meeting into 80% by very good category. Student’ activity in the first cycle at the first meeting is 50% by less category, and in the second meeting is 57% by fair category. The second cycle in the first meeting is 67% by good category and the second meeting is 77% by good category. Based on this research it can be concluded that the application of cooperative learning model make a match type can increase the science learning result of grade IV SDN 005 Lenggadai Hilir.Keywords: Cooperative Learning Model Make a Match Type, Science Learning Result